(untitled) (Education in the 21st Century, 2025)
A brief introduction. The most important scientific achievement of the last era is the development and implementation of computer information technologies in almost all spheres of life. Artificially loaded electronic devices have become the ideal of human intelligence. However, computer literacy often provides lifeless and non-deterministic information to children, which negatively affects their emotional, moral and spiritual development. At the beginning of the 19th century, psychologist, philosopher, pedagogue Georgi Gurdjieff expressed his fears about this. He mentioned the danger of people turning into a machine. Development and progress should not lead to people becoming a biorobot, a biological machine. The philosophy of education, having passed through spiritual and materialistic ideological stages in its development, recognizes that today the age of reason gives way to the age of awareness. The task of pedagogy is to educate a conscious person who consciously approaches the choice of his life path and scientific and technical progress. The article presents the importance of entertainment culture formation in the process of personality development and self-formation. Ever since antiquity, leisure has been considered a special activity, a special energy that was the language of cosmic harmony and through which man could reveal his potential by personalizing the cosmic intelligence. The elite of the 20th-21st century invented quasi-rest for the majority, which, subsequently dehumanizing the human and dignified with the help of propaganda through infernal energy, forms a new reality, teaching how to live, think, and nourish the spiritual. Depreciating the spiritual and intellectual world of people, the elite strives to deprive them of their ability to work independently. Leisure, having turned into entertainment, became a weapon aimed at destroying a person. That is why today it is extremely important to return to the origins of leisure culture, to properly organize the conscious synthesis of reason, emotions and imagination in children - a process in which something new, moral and human is born. Only in this way will the human mind be able to save the planet Earth from catastrophes and destruction.